2021
DOI: 10.1073/pnas.2119237119
|View full text |Cite
|
Sign up to set email alerts
|

Members of the KCTD family are major regulators of cAMP signaling

Abstract: Cyclic adenosine monophosphate (cAMP) is a pivotal second messenger with an essential role in neuronal function. cAMP synthesis by adenylyl cyclases (AC) is controlled by G protein–coupled receptor (GPCR) signaling systems. However, the network of molecular players involved in the process is incompletely defined. Here, we used CRISPR/Cas9–based screening to identify that members of the potassium channel tetradimerization domain (KCTD) family are major regulators of cAMP signaling. Focusing on striatal neurons,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 69 publications
1
29
0
Order By: Relevance
“…One simple model is that KCTD12 sequesters Gβγ subcomplexes produced under agonist-induced conditions, thus depleting G protein heterotrimers available for reactivation after prolonged agonist exposure ( Figure 6B ). While other possibilities cannot be presently excluded, and we note recent evidence for an additional effect of KCTD12 on adenylyl cyclase activity, 38 this simple model is attractive because it is sufficient to explain KCTD12 affecting both cAMP and GIRK signaling, as well as enhancing desensitization without changing the acute agonist response. Given that EYA4 and KCTD12 interact with the dissociated G protein subunits rather than with the receptor itself, we conclude (1) that they might regulate G protein signaling beyond MOR and (2) that GPCR-APEX has the sensitivity to monitor a proximal interaction network beyond its direct and indirect interactor partners.…”
Section: Discussionmentioning
confidence: 88%
“…One simple model is that KCTD12 sequesters Gβγ subcomplexes produced under agonist-induced conditions, thus depleting G protein heterotrimers available for reactivation after prolonged agonist exposure ( Figure 6B ). While other possibilities cannot be presently excluded, and we note recent evidence for an additional effect of KCTD12 on adenylyl cyclase activity, 38 this simple model is attractive because it is sufficient to explain KCTD12 affecting both cAMP and GIRK signaling, as well as enhancing desensitization without changing the acute agonist response. Given that EYA4 and KCTD12 interact with the dissociated G protein subunits rather than with the receptor itself, we conclude (1) that they might regulate G protein signaling beyond MOR and (2) that GPCR-APEX has the sensitivity to monitor a proximal interaction network beyond its direct and indirect interactor partners.…”
Section: Discussionmentioning
confidence: 88%
“…In previous work, we examined the opposite hypothesis. We demonstrated that GPCR stimulation of cAMP generation was significantly augmented during loss of KCTD (2, 5, or 17) in primary striatal neurons, an effect attributed to increased level of Gβγ ( 25 ). Here, we found the corollary effect of KCTD overexpression in primary striatal neurons: KCTDs that interact with Gβγ significantly reduced stimulatory dopamine receptor signaling to cAMP.…”
Section: Discussionmentioning
confidence: 96%
“…We utilized the cAMP pathway to examine how principles that guide KCTD–Gβγ interaction impact signal transmission in live cells. This was a rational starting point given significant alterations in cAMP signaling have been linked to KCTD knockout ( 24 , 25 ) whereas KCTD overexpression influence downstream to cAMP has not yet been reported. Future studies in additional Gβγ-dependent signaling modalities, such as K + flux through GIRK channels, will be of great interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, KCTD17 (Carpenter) and other KCTD family members regulate cAMP signaling 51 and are implicated in neurological disorders 52 . As well, CARTPT (Carpenter, Walker) is a prepropeptide related to the addiction gene CART (Cocaine and Amphetamine Regulated Transcript) 53,54 .…”
Section: Discussionmentioning
confidence: 99%